Earthquake design practice for buildings - Booth, E. D. (ICE Publishing, 2014)
'Earthquake Design Practice for Buildings' is an internationally applicable, practical guide for engineers to the seismic design of buildings for earthquake-resilient communities. In its third edition, it continues to provide comprehensive, practical, easy to read advice on the technical issues that have to be considered in the seismic design of buildings. It has been extensively updated and expanded, with completely new material added on socio-economic factors, recent technologies for earthquake resistance, displacement-based design, assessment of liquefaction potential and new developments in the seismic-resisting design and analysis of concrete, steel, timber and masonry structures.